The relationship of the level of job satisfaction and job performance of manufacturing employees of Caneland Sugar Corporation - Sta. Cruz, Eunice A.
Job satisfaction has been the subject of many researchers for it possible effects on performance yet the results were not quite so convincing. This study aims to find out whether a significant relationship exist between the level of job satisfaction and job performance given compensation, promotion, co-workers interrelationship, supervision-human relation and working condition are the areas which affect the level of satisfaction. The other variables investigated were age and the length of service of the employee in the company if they affect the level of satisfaction. The 49 respondents came from Caneland Sugar Corporation. The results were analyzed through a correlation matrix. A significant relationship exist between job satisfaction and performance but it is very low. As such the researchers, recommend that management should be concerned about this no matter how small is the degree of relationship.n